Emergent dimensions of community-oriented policing - Dario, Lisa M. (Crime & delinquency, 2022)
Community-oriented policing (COP) is arguably the most popular and most misunderstood policing philosophy. Definitional ambiguity contributes to this problem, hampering theoretical development, creative new strategies of implementation, and evidence-based policy. DiMaggio and Powell’s seminal piece on institutional isomorphism provides a framework for understanding the organizational vagueness of COP, including the processes of homogenization of priorities and structures across police organizations. We propose several new dimensions of COP, developed using police mission statements from a nationally representative sample of law enforcement agencies (N = 2,826). These emergent dimensions (Shallow Community-Oriented Policing, Responsivity, Legitimacy, Constitutionality, and Inclusivity) provide new avenues of theoretical consideration of the COP construct. Exploring these novel elements may strengthen existing community-oriented strategies and encourage creative policy suggestions.